Resources Optimization in Underground Gold Mining Case Study the Kubang Cicau Gold Vein in Pongkor Area, West Java, Indonesia. Issue 1 (1st May 2022) - Akmal, M.; Widodo, L.E.; Heriawan, M.N.; Rosyid, F.A.; Trilaksana, A.R.
Abstract: Mining activities are typically controlled by the smallest mining units (SMU). These SMUs comprise mining blocks with dimensions that are generally adjusted to the mining equipment used as well as various geotechnical factors. In addition to SMUs, the smallest mining decision unit (SMDU), which is a collection of several SMU blocks, is usually established. In this paper, the SMDU is represented by an underground (UG) mining panel. This paper presents the results of a study on the optimization of gold resource in SMU blocks within SMDU and cut-off grade (CoG) variations. The study focuses on how to design a panel as an SMDU that is based on a weekly production quota that defines an optimum weekly rate of production that meets processing and milling capacities. The UG mining scheme in this paper is realized using a level, a panel, and SMU blocks. The level represents the progress of the mining in a vertical direction, while the panel represents the progress of the mining in a horizontal direction. Acting as the objective functions are the ore tonnage and gold mass. In relation to the gold mass, the goal is to reach the optimum level within the SMDU and fulfill the constraint function through the number of SMU blocks within the SMDU and the range of CoG variations. The optimization process was conducted using a genetic algorithm scheme. Kubang Cicau Vein B at Pongkor Gold Mine Business Unit was selected for the case study.